Canonical and non-canonical roles for ATG8 proteins in autophagy and beyond - Reid, Steven Edward; Kolapalli, Srinivasa Prasad; Nielsen, Thorbjørn M.; Frankel, Lisa B. (Frontiers in Molecular Biosciences, 2022)
During autophagy, the ATG8 family proteins have several well-characterized roles in facilitating early, mid, and late steps of autophagy, including autophagosome expansion, cargo recruitment and autophagosome-lysosome fusion. Their discovery has importantly allowed for precise experimental monitoring of the pathway, bringing about a huge expansion of research in the field over the last decades. In this review, we discuss both canonical and non-canonical roles of the autophagic lipidation machinery, with particular focus on the ATG8 proteins, their post-translational modifications and their increasingly uncovered alternative roles mediated through their anchoring at different membranes. These include endosomes, macropinosomes, phagosomes and the plasma membrane, to which ATG8 proteins can bind through canonical or alternative lipidation. Beyond new ATG8 binding partners and cargo types, we also explore several open questions related to alternative outcomes of autophagic machinery engagement beyond degradation. These include their roles in plasma membrane repair and secretion of selected substrates as well as the physiological implications hereof in health and disease.